2007
DOI: 10.1099/mic.0.2006/003483-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium tropici response to acidity involves activation of glutathione synthesis

Abstract: Rhizobium tropici CIAT899 displays intrinsic tolerance to acidity, and efficiently nodulates Phaseolus vulgaris at low pH. By characterizing a gshB mutant strain, glutathione has been previously demonstrated to be essential for R. tropici tolerance to acid stress. The wild-type gshB gene region has been cloned and its transcription profile has been characterized by using quantitative real-time PCR and transcriptional gene fusions. Activation of the gshB gene under acid-stress conditions was demonstrated. gshB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
1
18
0
1
Order By: Relevance
“…A study by Küçük and Kivanç indicates that extreme values of pH result in dramatic decreases in EPS yields, particularly in the acidic range (Küçük and Kivanç 2009). Similar results have been observed by others; while the pH optimum for exopolysaccharide production depends on the individual bacterial species, for most species, it tends to be near neutrality (Williams and Wimpenny 1977;Vermani et al 1997) and constant (Morin 1998). We have found this to be the case with R. tropici where our two acidic trials formed less EPS than the trials cultured closer to neutral pH.…”
Section: Discussionsupporting
confidence: 69%
“…A study by Küçük and Kivanç indicates that extreme values of pH result in dramatic decreases in EPS yields, particularly in the acidic range (Küçük and Kivanç 2009). Similar results have been observed by others; while the pH optimum for exopolysaccharide production depends on the individual bacterial species, for most species, it tends to be near neutrality (Williams and Wimpenny 1977;Vermani et al 1997) and constant (Morin 1998). We have found this to be the case with R. tropici where our two acidic trials formed less EPS than the trials cultured closer to neutral pH.…”
Section: Discussionsupporting
confidence: 69%
“…The CIAT 899 and PRF 81 genomes encoded a homologue of kcsA , a Streptomyces lividans ion channel that opens at low pH allowing K + entrance into the cell. Riccillo et al [24] found that the glutathione synthase gshB gene is required for CIAT 899 tolerance to acidic stress, its activation occurring under low-pH conditions [174]. The inability of a CIAT 899 gshB mutant to grow in low-pH media was related to a diminished capacity to accumulate K + at low pH, and it was proposed that a KefB/KefC glutathione-regulated K + efflux transporter may be too active in the absence of glutathione [24].…”
Section: Resultsmentioning
confidence: 99%
“…A series of authors demonstrated that the efficacy of nodule formation of R. tropici is increased under acidic conditions, whereas R. leguminosarum, on the contrary, exhibited decreased nodule formation under the same conditions (Martínez Romero et al, 1991;Muglia et al, 2007). We revealed high homology of some symbiotic genes of these bacteria with analogical It is possible that Agrobacterium sp.…”
Section: Resultsmentioning
confidence: 63%